DAMPAK PANDEMI COVID-19 DALAM PERSPEKTIF GENDER DI INDONESIA - Ikfina Chairani (Jurnal Kependudukan Indonesia, 2020)
The COVID-19 outbreak has inevitably changed the situation in Indonesia and might bring a threat to gender equality. This short paper aims to explain the impact of the COVID-19 pandemic on women from health, economic, and social aspect in Indonesia. First, from the health aspect, women are vulnerable to COVID-19 since they play the main role in the care economy. Also, the pandemic situation has changed the regulation of reproductive health services and might intensify the unmet need of women on reproductive health care. Second, from the economic aspect, the pandemic has hit Indonesiaâ€™s economic situation and increases the unemployment rate as well as the informal worker on women. In addition, women also might be harder to return to market labor since it might be a limitation after the pandemic. Third, from the social aspect, due to working from home (WFH) regulation, women more likely to face a double burden to balance their productivity and domestic work. Not to mention that during the pandemic, the domestic violence to women has increased yet slower the responsiveness of the stakeholder to handle the reports.Â